Fluorescence angiography in laparoscopic low rectal and anorectal anastomoses with pinpoint perfusion imaging‐ a critical appraisal with specific focus on leak risk reduction. (October 2015) - James, D. R. C.; Ris, F.; Yeung, T. M.; Kraus, R.; Buchs, N. C.; Mortensen, N. J.; Hompes, R. J.
Abstract: Background and aims: Anastomotic dehiscence is one of the most feared complications in colorectal surgery leading to significant morbidity and mortality. Progressively lower anastomoses are associated with a greater leak rate. One of the key factors is the perfusion of the bowel to be joined. Presently, surgeons rely on a variety subjective measures to determine anastomotic perfusion and mechanical integrity however these have shortcomings. The aim of this paper is to appraise the literature on the use of fluorescence angiography (FA) in laparoscopic rectal surgery. Materials and methods: A Pubmed search was undertaken using terms 'fluorescence angiography' and 'rectal surgery'. The search was expanded using the related articles function. Studies were included if they used FA specifically for rectal surgery. Outcomes of interest including anastomotic leak rate, change of operative strategy and time taken for FA were recorded. Results: Eleven papers detailing the use of FA in rectal surgery are outlined demonstrating that this technique may change operative strategy and lead to a reduction in anastomotic leak rate. Conclusion: In this paper, we discuss assessment of colorectal blood supply using FA and how this technique holds great potential to detect insufficiently perfused bowel. In so doing, the operator can adjust their operative strategy to mitigate these affects with the aim of reducing the complications of anastomotic leak and stenosis. However, it is highlighted that there is a clear need for randomised controlled trials in order to determine this definitively.